Model Pemberdayaan Berbasis Pemanfaatan Sumberdaya Alam Berkelanjutan: Studi pada Program Energi Terbarukan di Kabupaten Jombang - Magalhaes, Lucas; Hartanto, Arif Dwi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
The concept of economic development that is based on villages so far still causes debate. Supporting arguments say that village empowerment is the key to the success of inclusive economic development. The aim is to create sustainable economic development based on creating high economic value. Based on this, the main objective of this research is to examine how much impact the new and renewable energy program in Jombang has had on the empowerment of rural communities. Based on the Cluster Analysis method, the new and renewable energy program is proven to have implications for the empowerment of rural communities as indicated through two things, namely: (i) an increase in income especially the poor; and (ii) local communities are able to develop village development planning and implementation. This proves that the new and renewable energy program has been able to realize the independence of the village. Therefore, this program is expected to be a proliferation of empowerment models that are based on sustainable use of natural resources.